2004
DOI: 10.1097/00001756-200412030-00020
|View full text |Cite
|
Sign up to set email alerts
|

ApoE isoform affects LTP in human targeted replacement mice

Abstract: Inheritance of the epsilon4 allele for apolipoprotein E (apoE) increases the risk of Alzheimer disease and memory impairment, whereas epsilon2 decreases these risks compared with the most common epsilon3 allele, but the mechanism for these effects is unknown. Long-term potentiation (LTP) is an experimentally induced increase in synaptic efficacy that models memory. Using hippocampal slices from wild type (WT), apoE knockout (apoE-KO), and targeted replacement mice expressing human apoE2, E3, or E4 (apoE-TR) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 25 publications
6
84
1
Order By: Relevance
“…It is suggested that apoE4 is able to promote Aβ aggregation and/or reduce the clearance of amyloid plaques [44]. Moreover, it was observed that human apoE4 knock-in mice show a decrease in long-term potentiation, excitatory synaptic transmission and dendritic arborization, which determine impaired synaptic and cognitive functions [45][46][47][48]. These experimental data corroborate with clinical evidence, demonstrating that apoε4 homozygosity confers a substantial cognitive function decline in persons aged 35 years or older [49].…”
Section: Alzheimer's Diseasesupporting
confidence: 59%
“…It is suggested that apoE4 is able to promote Aβ aggregation and/or reduce the clearance of amyloid plaques [44]. Moreover, it was observed that human apoE4 knock-in mice show a decrease in long-term potentiation, excitatory synaptic transmission and dendritic arborization, which determine impaired synaptic and cognitive functions [45][46][47][48]. These experimental data corroborate with clinical evidence, demonstrating that apoε4 homozygosity confers a substantial cognitive function decline in persons aged 35 years or older [49].…”
Section: Alzheimer's Diseasesupporting
confidence: 59%
“…It has been shown in vitro and in vivo that APOE 4 inhibits clearance, facilitates production and promotes deposition of A ␤ , ultimately leading to plaque formation [34] . The ability to form memories is reduced in APOE 4 transgenic mice models when compared to wild-type mice [38] . The increased lipid burden within the brain and impaired lipid homeostasis may then contribute to increased oxidative stress and lead to cellular damage through lipid peroxidation, decreased vascular perfusion and development of an immune response.…”
Section: Apolipoprotein Ementioning
confidence: 96%
“…Features of AD pathology in these animals include reduced numbers of presynaptic terminals in mice expressing apoE4 with (54,64) or without (53,66,68) expression of human amyloid precursor protein (APP), increased plaque deposition in apoE4 mice expressing APP (64), increased phosphorylation of tau (65)(66)(67), impaired learning and memory (55,69), and altered long-term potentiation (77).…”
Section: Apoe and Admentioning
confidence: 99%